H5N1 influenza: A protean pandemic threat - Guan, Y. (National Academy of Sciences, 2004)
Infection with avian influenza A virus of the H5N1 subtype (isolates A/HK/212/03 and A/HK/213/03) was fatal to one of two members of a family in southern China in 2003. This incident was preceded by lethal outbreaks of H5N1 influenza in waterfowl, which are the natural hosts of these viruses and, therefore, normally have asymptomatic infection. The hemagglutinin genes of the A/HK/212/03-like viruses isolated from humans and waterfowl share the lineage of the H5N1 viruses that caused the first known cases of human disease in Hong Kong in 1997, but their internal protein genes originated elsewhere. The hemagglutinin of the recent human isolates has undergone significant antigenic drift. Like the 1997 human H5N1 isolates, the 2003 human H5N1 isolates induced the overproduction of proinflammatory cytokines by primary human macrophages in vitro, whereas the precursor H5N1 viruses and other H5N1 reassortants isolated in 2001 did not. The acquisition by the viruses of characteristics that enhance virulence in humans and waterfowl and their potential for wider distribution by infected migrating birds are causes for renewed pandemic concern.